Strategies Of Islamic Religious Education (PAI) Teachers In Teaching During The Era Of Industrial Revolution 4.0 - Zamroni, Sofyan; Arifin, Zainal (STAI Miftahul Ula Nganjuk, 2024)
This research aims to explore and describe the strategies employed by Islamic Religious Education (PAI) teachers in adapting to the challenges posed by the Industrial Revolution 4.0, particularly focusing on their impact on the teaching and learning process at SMAN 1 Kertosono, Nganjuk Regency. The advent of the Industrial Revolution 4.0 has introduced significant changes to the educational landscape, especially in the dynamic between teachers and students. With the easy accessibility of digital technology and information, the traditional role of teachers as the primary source of knowledge has been diminished. This shift presents several challenges, including digital addiction, cyberbullying, and a decline in students’ moral values, which have been evident at SMAN 1 Kertosono. To address these issues, the study utilizes a qualitative descriptive method to analyze the strategies employed by PAI teachers to enhance the learning experience in this digitally-driven environment. The findings highlight that PAI teachers have adopted various innovative strategies to engage students effectively, such as integrating digital tools with moral education to foster both academic and ethical development. These strategies aim to create a positive learning environment that addresses the unique challenges posed by the digital era, ensuring that students not only excel academically but also maintain strong moral values. Overall, the study reveals how PAI teachers are successfully navigating the challenges of the Industrial Revolution 4.0, providing a model for adapting traditional education to the demands of modern technological advancements